Management model to reduce the costs of non-quality with the Lean Six Sigma methodology in tissue paper converters - Chirinos Magallanes, Daniel Alberto (2025)
The impact of non-quality costs generated by poor management of quality standards compliance is analysed. The objective is to determine the influence of a mana- gement model based on the Lean Six Sigma methodology in reducing these costs. The most modern converter line in technology and with a higher production capacity was selected as the unit of analysis, applying the phases of the DMAIC cycle: define, measure, analyse, improve and control. As a result, the cost of non-quality was reduced by 40 % equivalent to S/.901 236; the indicator of defective products decreased from 3,58 % to 2,11 % and the sigma level increased from 3,38 to 4,24. The limitation was disclosure of costs broken down by confidentiality; however, the findings have practical implications for other industries seeking to reduce their non-quality costs through Lean Methodologies.